KONSEP, TUJUAN, DAN FUNGSI ADMINISTRASI PENDIDIKAN - Ingka Asmariyanti; Fadhila Ramadhanty; Fuji Angraini Ritonga; Nurselihatun; Disnawati; Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the field of educational administration, principles, objectives and functions cannot be separated. These things are interrelated and cannot be separated because all three have their respective roles in educational administration so that the educational administration process can run effectively, efficiently and conducively in achieving the goals of the relevant institution. The method used in this journal is the literature review method and qualitative descriptive analysis techniques. The research results from this journal provide an in-depth understanding of the concepts, goals and functions of educational administration. This journal also includes several relevant expert opinions in the context of educational administration, adding to the accuracy and diversity of the information presented. that the concept of educational administration has developed from the scope of the company or industrial sector and entered the educational curriculum. Thus, educational administration has a very important role in achieving educational goals and improving the overall quality of education.